Development of basic-needs experience and finance-related attitude through game-based learning: The role of game mechanics and debriefing - Liane Platz; Michael Juettler (PLoS ONE, 2025)
Game-based learning (GBL) supports the development of domain-specific competencies, especially knowledge, more effectively than traditional learning methods. However, it is still unclear which elements of GBL positively impact learning outcomes such as motivation and attitudes. This study involved 293 upper-secondary students in a quasi-experiment using a 2 × 2 control group design with five measurement points to test the effects of game mechanics and reflection prompts. This approach aimed to assess their effects on the basic needs experience and attitude towards financial planning among upper-secondary school students. We applied a multivariate analysis of variance and a moderated mediation path model to address two questions: (a) whether game experiences differ depending on core mechanics and reflection prompt design, and (b) whether game mechanics influence changes in finance-related attitude through basic needs experience, moderated by reflection prompts. The findings demonstrate that games offering a higher degree of strategic decision-making options and direct reflection prompts positively impact students’ basic needs experience with a moderate effect size. However, the path model did not reveal a group-specific influence on finance-related attitude. Therefore, this study provides initial results from an experimental approach to identifying the influence of different game mechanics and reflection prompts, offering valuable empirical insights into the implementation of GBL in educational settings across domains.